Corrected Long-Term Time-Average Sound Level of Amplitude-Modulated Wind Turbine Noise - Rufin Makarewicz; Maciej Buszkiewicz (Archives of Acoustics)
Amplitude modulated noise from a single wind turbine is considered. The time-varying modulation depth D_m and the short time-average sound level L_Aeq,τ (with τ = 20 s) are measured at the reference distance d_*. Due to amplitude modulation, a penalty has to be added to L_Aeq,τ. The paper shows how to calculate the corrected long-term time-average sound level L ̂_AeqT (with T >> 20 s), which accounts for amplitude modulation, at any distance d ≠ d_* from the wind turbine. The proposed methodology needs to be tested by research